2005
DOI: 10.1007/s10038-005-0318-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of alcohol dehydrogenase 2*1 allele with liver damage and insulin concentration in the Japanese

Abstract: The Japanese have a polymorphism in the alcohol dehydrogenase 2 gene (ADH2). The alleles of ADH2 (ADH2*1 and ADH2*2) encode more active and less active forms for ethanol metabolism, respectively. We examined whether liver damage and the insulinglucose axis vary according to ADH2 genotype in the Japanese. The 2,232 subjects (1,126 men and 1,106 women) were recruited from a population-based prospective cohort study. Clinical evaluations including alcohol consumption, percentage of alcohol drinkers, plasma glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
(28 reference statements)
1
9
1
Order By: Relevance
“…Alternatively, alcohol may be protective but possession of ALDH2*2 alleles could be associated with both lower blood glucose and a greater inclination to never-drinking. However, the limited evidence available does not suggest that this is the case 22 23…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, alcohol may be protective but possession of ALDH2*2 alleles could be associated with both lower blood glucose and a greater inclination to never-drinking. However, the limited evidence available does not suggest that this is the case 22 23…”
Section: Discussionmentioning
confidence: 99%
“…5 However, alcohol-inducible CYP2E1 also has an important role in alcohol metabolism and mediate liver impairment among variety of alcohol drinkers. 2 Although the role of CYP2E1 in alcohol-mediated liver toxicity is well known, similar studies are limited in extra-hepatic cells, especially cells from the CNS.…”
mentioning
confidence: 99%
“…Indeed, the prevalence of ADH1B and ALDH2 of the subjects in this study was similar to those reported in Japanese population. It has been reported that differences in these polymorphic ethanol-metabolizing enzymes influence FPG level25, glycemic control26, insulin level27 and risk for diabetes28. Thus, we speculate that differences in the distribution of polymorphic ethanol-metabolizing enzymes between Asians and Caucasians may be responsible for the differences in the relation between alcohol intake and hepatic insulin sensitivity.…”
Section: Discussionmentioning
confidence: 76%